Integrating contemporary accounting and international business research: progress so far and opportunities for the future - Filatotchev, Igor; Fisch, Jan Hendrik; Livne, Gilad; Carmona, Salvador (Routledge, 2024)
To date,the accounting and international business (IB) research fields have been developing rather independently,although some cross-discipline fertilisation is emerging. This paper aims to illustrate the conceptual and empirical bridges between the two disciplines. Specifically,we highlight how contributions originating in either field have influenced theory and research in such diverse areas as corporate governance,risk management,taxation and strategic decision making in multinational enterprises (MNEs). Further,we identify examples where attention by accounting researchers to the IB literature has resulted in innovative research,including studies focusing on control systems and financial reporting in MNEs. Based on our discussion of the state of mutual contributions between the disciplines,we highlight various areas where future research could benefit from further integration of the accounting and IB literatures. © 2023 The Author(s). Published by Informa UK Limited,trading as Taylor & Francis Group.
Keywords: Corporate governance; Financial reporting; Multinationals; Strategic decision making; Sustainability; 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 17 - Alianzas para lograr los objetivos; ODS 8 - Trabajo decente y crecimiento económico; ODS 4 - Educación de calidad